2008
DOI: 10.1002/pc.20623
|View full text |Cite
|
Sign up to set email alerts
|

Study of the modification of the properties of (PP/EPR) blends with a view to preserving natural resources when elaborating new formulation and recycling polymers

Abstract: International audienceThe aim of the present work is to study how CaCO3, very abundant on earth, can be blended with polypropylene/ethylene propylene rubber (PP/EPR) either to preserve natural resources when elaborating virgin formulations or to simulate mixtures of waste made of CaCO3 filled PP with PP/EPR which could result from end-of-life-vehicles (ELV). The article focuses on the studies of PP/EPR blends, used in the manufacture of automobile fenders, in the presence of nano-CaCO3 and compatibilizers. Ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Similar observations have been reported that the thermal stability of polypropylene/layered silicate nanocomposites was improved by a physical barrier effect; hence it is enhanced by ablative reassembling of the silicate layer [147]. It can also explained that may be due to the filler effect that is prominent and retards the degradation of TPE gels and the retardation effect is attributed to the interaction between nanoparticles and macroradicals generated during the degradation process.…”
Section: Thermal Propertysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar observations have been reported that the thermal stability of polypropylene/layered silicate nanocomposites was improved by a physical barrier effect; hence it is enhanced by ablative reassembling of the silicate layer [147]. It can also explained that may be due to the filler effect that is prominent and retards the degradation of TPE gels and the retardation effect is attributed to the interaction between nanoparticles and macroradicals generated during the degradation process.…”
Section: Thermal Propertysupporting
confidence: 83%
“…An alternative possibility is to include elastomer granulate in a matrix of elastomer with a different composition, using compatibilizer to achieve acceptable properties [146,147]. It should be noted though that meeting performance requirements in the case of renewed recycling of elastomers composed of more than one type of polymer may be more difficult than in the case that one type of polymer is present [43].…”
Section: Recycling Options For Elastomeric Nanocompositesmentioning
confidence: 99%
“…A complex mixture containing calcium carbonate was studied to solve recycling problem, and to facilitate the recovery of PP composites with simplified sorting and lower levels of purity . Nano‐CaCO 3 fillers were mixed to (PP/EPR) based formulations in the perspective of processing more complex blends when recycling . Calcium carbonate was also considered as impurity in postconsumer PP .…”
Section: Introductionmentioning
confidence: 99%
“…The POE, ethylene-propylene-diene monomer (EPDM), and styreneethylene-butylene-styrene (SEBS) elastomer were used as toughening agents, which were dispersed in the resin matrix in an appropriate manner. However, the stiffness, strength, and heat distortion temperature of the PP were reduced to a certain degree [7][8][9].…”
Section: Introductionmentioning
confidence: 99%